Development of the Bone Phenotype and microRNA Profile in Adults With Low‐Density Lipoprotein Receptor‐Related Protein 5–High Bone Mass (LRP5‐HBM) Disease. (1st September 2021) - Lauterlein, Jens‐Jacob Lindegaard; Gossiel, Fatma; Weigl, Moritz; Eastell, Richard; Hackl, Matthias; Hermann, Pernille; Bollerslev, Jens; Frost, Morten
ABSTRACT: Pathogenic variants in the Wnt‐pathway co‐receptor low‐density lipoprotein (LDL) receptor‐related protein 5 (LRP5) cause high bone mass (LRP5‐HBM) due to insensitivity to the endogenous antagonist of Wnt‐signaling. Although indicating incessant progression of BMD and biomarkers reflecting bone formation, this has not been confirmed in individuals with LRP5‐HBM. We investigated how the LRP5‐HBM bone phenotype changes with age in adults and is associated with quantitative changes of bone turnover markers and bone‐related microRNAs (miRNAs) in the circulation. Whole body, lumbar spine, total hip, and femoral neck areal BMD (aBMD) and radial and tibial bone microarchitecture and geometry were assessed using DXA and HR‐pQCT scans of 15 individuals with LRP5‐HBMT253I (11 women; median age 51 years; range, 19 to 85 years) with a time interval between scans of 5.8 years (range, 4.9 to 7.6 years). Fasting P1NP and CTX were measured in 14 LRP5‐HBMT253I individuals and age‐, sex‐, and body mass index (BMI)‐matched controls, and 187 preselected miRNAs were quantified using qPCR in 12 individuals and age‐, sex‐, and BMI‐matched controls. DXA and HR‐pQCT scans were assessed in subjects who had reached peak bone mass (aged >25 years, n  = 12). Femoral neck aBMD decreased by 0.8%/year ( p  = 0.01) and total hip by 0.3%/year, and radial volumetric BMD (vBMD) increased 0.3%/year ( p  = 0.03). Differences in bone turnover markers at follow‐up were not observed. Compared to controls, 11 of the 178 detectable miRNAs were downregulated and none upregulated in LRP5‐HBM individuals, and five of the downregulated miRNAs are reported to be involved in Wnt‐signaling. Bone loss at the hip in LRP5‐HBM individuals demonstrates that the bone phenotype does not uniformly progress with age. Differentially expressed miRNAs may reflect changes in the regulation of bone turnover and balance in LRP5‐HBM individuals. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.